The Evaluasi Penggunaan Obat Kemoterapi Pada Pasien Kanker Serviks di RSUP Fatmawati Periode 1-30 September 2024 - Dharmawan, Fahmi (RSUP Fatmawati, 2025)
In Indonesia, the prevalence of cervical cancer, one of the most prevalent and fatal cancers in women, is still rising. The purpose of this study is to assess the utilization of chemotherapy medications in patients with cervical cancer at Fatmawati Central General Hospital during the month of September 2024. Descriptive research using a retrospective approach is the methodology employed, and data from 18 chemotherapy patients' medical records is analyzed. According to the 2020 National Comprehensive Cancer Network (NCCN) recommendations, evaluation was conducted using the proper criteria for patient, medication, dosage, and indication. The study's findings demonstrated that there were no contraindications and that 100% of patients received treatment in accordance with the indication. Combining Paclitaxel with Carboplatin is the most used type of chemotherapy regimen. Not all doses were administered in accordance with the patient's Body Surface Area (LPT) calculation, as evidenced by the average accuracy of all doses administered, which was 78.96%. Although this study paints a favorable picture of the suitability of chemotherapy medication use in these facilities, it also emphasizes the necessity of raising knowledge and educating people about cervical cancer treatment in order to enhance overall therapeutic results.